KILLING TWO BIRDS WITH A STONE: MERGING READING AND WRITING ACTIVITIES THROUGH BLACKOUT POETRY - Sulastri, Fera; Sri, Melisa; Belkis, Salma Ayu (Universitas Muhammadiyah Metro, 2023)
This study investigates students' perceptions of writing online blackout poetry in an elective course called Children's Literature. A descriptive case study is purposively used to explore their perceptions of the advantages of writing online blackout poetry on their reading and writing skills and the obstacles in doing the activity. Fifty-one students of children's literature writing blackout poetries are the research participants. Close-ended and open-ended questionnaires were used for the data collection. Meanwhile, the data were analyzed thematically using the framework of Braun and Clarke (2006). The findings show that students have a positive perception of writing blackout poetry. They believe that the activity is challenging and promotes their creativity. Furthermore, it is regarded as a media that merges reading and writing activities. However, it is found that blackout poetry has limited word expression. Despite its weaknesses, this study implies that blackout poetry can promote creativity and reading and writing activities in the EFL context.